The use of multimedia technologies in robotics lessons as the development of cognitive activity (Journal of Educational Sciences, 2023)
In the environment of educational robotics, the introduction of new pedagogical technologies isrelevant. Robotics is at the junction of promising fields of knowledge: mechanics, electronics, automation,assembly, programming, circuit engineering and technical design. The purpose of the article is toanalyze the methodology of teaching the basics of robotics using multimedia technologies at each stageof education and the use of multimedia software in the classroom. The authors of the article have developedDigital educational resources for the study of robotics. These resources are an auxiliary tool for thediversity of the lesson. With the help of this software product, robotics training becomes more accessibleand convenient. Multimedia allows you to combine verbal and visual-sensory information, which helpsto increase the motivation of students, create certain learning parameters and develop cognitive activity.When organizing educational material, the teacher should focus on the activation of cognitive activityof students. In the classroom, not all students turn on active cognitive activity. Active teaching methodsare used to purposefully influence this activity. The very name contains the essence of the activemethod – it is not simple memorization, but the active intellectual activity of students.The result of scientific and methodological research was the design and development, approbationof the DER with the help of which it becomes possible to conduct lessons using multimedia technologies.Key words: educational robotics, multimedia technologies, cognitive activity, digital educationalresources.